EDUKASI TENTANG RISIKO INFEKSI PARASIT USUS PADA PERILAKU OPEN DEFECATION SEBAGAI UPAYA MENINGKATKAN PENCAPAIAN OPEN DEFECATION FREE YANG MENUNJANG PENINGKATAN DERAJAT KESEHATAN ANAK INDONESIA - Mutiara, Hanna; Lisiswanti, Rika; Ramadhian, Muhammad Ricky; Islami, Suryadi; Apriliana, Ety; Fatriyadi, Jhons (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Sustainable Development Goals (SDGs) have set 17 development goals that must be achieved by 2030. One of the goals is to ensure a healthy and prosperous life for all communities. This health-related component is related to access to clean water and sanitation to create a healthy environment and will reduce the risk of transmission of various infectious diseases, especially diarrhea. Diarrhea is currently one of the biggest killers of toddlers in Indonesia. This disease is an environmental-based disease that is closely related to the practice of open defecation. Diarrhea can be caused by several etiologies, including intestinal parasitic diseases. One of the targets set out in the SDGs related to healthy sanitation is access to achieving stop open defecation behavior. Stichting Nederlandse Vrijwilligers (SNV) in April 2022 stated that of the 9 million residents in Lampung, around 1 million people do not have access to a toilet or still practice open defecation. Of the 15 city districts in Lampung Province, only five regions have implemented ODF. The aim of this activity is to make an effort to improve children's health status, in particular increasing knowledge about the risk of intestinal parasite infection in open defecation behavior. This is expected to increase motivation and practice to stop open defecation so that it can increase the achievement of open defecation free in Indonesia, especially Lampung Province. It is hoped that this will improve the level of health, especially for Indonesian children who are the nation's next generation.